Analysis of gray hole attack on MANETs using different MANET routing protocols / Yashar AzabDaftari - AzabDaftari, Yashar (2011)
According to recent technological advance in the electronic and wireless telecommunications, the performance and use of wireless technologies has increased tremendously. One such field, concerns mobile ad hoc networks (MANETs) in which mobile nodes organize themselves in a network without the help of any predefined infrastructure. The dynamic topology of MANETs allows nodes to join and leave the network at any point of time. This generic characteristic of MANET has rendered it vulnerable to security attacks. Securing MANETs is an important part of deploying and utilizing them, since they are often used in critical applications where data and communications integrity in important. However, due to security vulnerabilities of the routing protocols, wireless ad-hoc networks are unprotected to attacks of the malicious nodes. This study tries to compare of gray hole attack with two different routing protocols which called Ad-hoc on-demand Distance Vector (AODV) and Optimized Link State Routing Protocol (OLSR). Moreover simulate the behavior of these two protocols to show end to end delay packet loss and performance of the routings.